2005
DOI: 10.1097/01.mao.0000169051.69254.85
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Rehabilitation Therapy in Children

Abstract: Vestibular rehabilitation therapy seems to be a safe and efficacious therapeutic option in children with peripheral vestibular disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 10 publications
0
17
0
3
Order By: Relevance
“…Basing a clinical judgement on subjective opinion is very likely to give misleading results, especially if one bears in mind that even standardised tests have been shown to have a large amount of variability [19]. The provision of reference data is therefore needed for these commonly used clinical tests to minimise subjectivity in interpretation and so that appropriate management decisions, such as referral for vestibular rehabilitation [21] or occupational therapy can be made.…”
Section: Introductionmentioning
confidence: 97%
“…Basing a clinical judgement on subjective opinion is very likely to give misleading results, especially if one bears in mind that even standardised tests have been shown to have a large amount of variability [19]. The provision of reference data is therefore needed for these commonly used clinical tests to minimise subjectivity in interpretation and so that appropriate management decisions, such as referral for vestibular rehabilitation [21] or occupational therapy can be made.…”
Section: Introductionmentioning
confidence: 97%
“…The nine randomized controlled trials show significant improvements after vestibular rehabilitation in terms of anxiety and depression level (28), balance measures (27,29,30,33), ataxia (30), gaze stability (31), gait function (32), vertigo (34), independence (34), gait stability and gait velocity (35). The 12 interventions studies with a control group showed improvements in stability (38), posturography (39,43), fall reduction (39), vestibulospinal compensation (40), balance performance (37,41,47), absence of nystagmus (42), recovery of symptom in children with vestibular disturbances (43), improvements in patterns of head control using three-dimensional kinematics, improved independence (44), decreased vertigo (45), increased steadiness (45), improvement in self-perceived handicap and improvement in gait (47). The eight intervention studies without control group showed improvement in gait velocity (51), self-perceived handicap (49,53,54), posturography (53), timed up and go (53), improvement in quality of life (54) and in balance (48,55).…”
Section: Vestibular Rehabilitation For Vestibular Hypofunctionmentioning
confidence: 97%
“…In five of the studies, the patients had unilateral peripheral lesion (29,40,47,49,50); in 10, the patients had peripheral vestibular dysfunction without specification (31 Á33,37,42,44 Á46,48,54). One of the studies involved children (43); one studied patients with peripheral vestibular dysfunction and agoraphobia (41). Six of the studies concerned chronic vestibular dysfunction (27,28,30,39,51), one included patients with vestibulospinal reflex pathology (38), one patients with uni-or Figure 6.…”
Section: Vestibular Rehabilitation For Vestibular Hypofunctionmentioning
confidence: 99%
“…A manutenção do equilíbrio depende da integridade anatômica e funcional do aparelho vestibular, bem como da correlação entre os sistemas visual, proprioceptivo, musculoesquelético e centros nervosos [1][2][3][4][5][6][7][8][9][10][11] . O equilíbrio consiste na manutenção do centro de gravidade dentro da área da superfície de apoio e se apresenta de três formas: equilíbrio estático (exemplo: ficar parado em determinada posição); equilíbrio dinâmico, que é conseguido no movimento e que depende do dinamismo dos processos nervosos (exemplo: o andar) 12 ; equilíbrio recuperado, que é a qualidade física que explica a recuperação do equilíbrio numa posição qualquer (exemplo: salto do cavalo, saída da barra fixa, cortada no voleibol) 13 .…”
Section: Introductionunclassified
“…Por meio de programas de treinamento baseado em exercícios que envolvam o equilíbrio corporal (Exemplo: jogos com bola, trampolim acrobático, dança, entre outros), os surdos podem desenvolver estratégias posturais para superar ou compensar as eventuais dificuldades de equilíbrio 21 . Estas estratégias posturais são decorrentes da neuroplasticidade, a qual determina que as funções do sistema vestibular afetado possam ser compensadas por outros sentidos, atingindo-se um desenvolvimento semelhante aos dos sujeitos sem alterações no equilíbrio 4,7,14 . É a teoria da compensação 17,22 .…”
Section: Introductionunclassified